Evaluation of the efficacy of the childbirth grant in Korea 2006-2012 - LIM, Youngju (KDI School, 2015)
As local governments have competitively introduced childbirth grants to increase the total birth rate, there has been much debate on policy impact. Some research studies estimate the effectiveness of childbirth grants on the fertility rate; however, most used macro-level data that cannot cover the birth decisions of individual households. This study conducted empirical analysis to investigate the birth interval using micro panel data while taking note of the childbirth grant to minimize the debate stated above. Besides this, other factors affecting fertility were also examined for fertility policy implementation. By using KLIPS data (9th–15th), this study derived data of 978 mothers of newborn babies (born 2006–2015) and household. This research apprehended the general characteristics of the sample and the trends of the birth interval through Kaplan-Meier estimation. In addition, by using the Cox proportional hazard model, this study investigated economic factors (including the weekly wages of mothers, total household income, and labor force participation of mothers), socio-demographic factors (married age, education level, and the presence of grandparents), and childbirth grant policy on birth spacing. The results of this study are as follows: First, the birth interval from previous birth to next birth was about 33.3 months. In other words, children within a family were spaced an approximate average of 2.9 years apart. Second, the childbirth grant had no significant impact on the birth interval. It appeared that other policy measures were necessary to increase fertility while providing temporary financial transference. Third, the labor force participation of mothers, the weekly wage of mothers, and the age of marriage had a statistically significant impact on the birth interval. The birth interval of mothers who currently work was shorter than those of full-time mothers. Mothers who had a higher weekly wage tended to have a longer birth interval. The older the mother, the longer the birth interval. Thus, the labor market policies for women are one of fundamental issues related with low fertility problem. Despite its limitations, it is meaningful that this study assesses the longitudinal impact of childbirth grants on the birth interval based on micro-level KLIPS data for 2006–2012.
Thesis(Master) --KDI School:Master of Public Policy,2015